The relationship between the role of health workers and interest in using mow contraception - Nia Trisanti Sari; Ana Zumrotun Nisak; Dwi Astuti (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Long-term contraceptive methods are contraceptives that can be used for more than two years. Factors that can influence the selection of MOW contraception include health workers. Health workers, in addition to providing physical services, are authorised to carry out Communication, Education and Information (IEC) to prospective birth control users. Purpose: To analyse the relationship between the role of health workers on the interest in using MOW contraception. Method: This research method uses an analytic correlation approach. The population of this study consisted of all patients who used contraception at Sebening Kasih Tayu Pati Hospital, totalling 246 patients. The sample needed in this study was 61 respondents. The instruments used were a questionnaire of the role of health workers and a questionnaire of interest in using MOW contraception. Statistical analysis using chisquare was analysed using statistical techniques, namely the C correlation test with a confidence level of 95% (α = 0.05). Results: Respondents who rated the role of health workers as poor were mostly not interested in using MOW, namely 23 respondents (37.7%), while only 5 respondents (8.2%) were interested. In contrast, respondents who rated the role of health workers as good were mostly interested in using MOW, namely 27 respondents (44.3%), and only 6 respondents (9.8%) were not interested. Conclusion: There is a significant relationship between the role of health workers and interest in using MOW contraception. Suggestion: Midwives are advised to always invite fertile couples to be able to accept and take the time when given health education and can make the right decision to use effective family planning as needed.